The alchemist's cat - Jarvis, Robin, 1963- (Jarvis, Robin, 1963- Deptford histories, 2004)
Will Godwin escapes to London and becomes an assistant to the evil alchemist, Elias Spittle, who sends Will on an errand where he finds and rescues a mother cat and her kittens which sparks an extraordinary tale of sorcery and murder.